Exposure to Nanoplastics During Pregnancy Induces Brown Adipose Tissue Whitening in Male Offspring - Zhaoping Shen; Kai Tian; Jiayi Tang; Lin Wang; Fangsicheng Zhang; Lingjuan Yang; Yufei Ge; Mengna Jiang; Xinyuan Zhao; Jinxian Yang; Guangdi Chen; Xiaoke Wang (Toxics)
Background: Polystyrene nanoplastics (PSNPs) have been recognized as emerging environmental pollutants with potential health impacts, particularly on metabolic disorders. However, the mechanism by which gestational exposure to PSNPs induces obesity in offspring remains unclear. This study, focused on the whitening of brown adipose tissue (BAT), aims to elucidate the fundamental mechanisms by which prenatal exposure to PSNPs promotes obesity development in mouse offspring. Methods and Results: Pregnant dams were subjected to various doses of PSNPs (0 µg/µL, 0.5 µg/µL, and 1 µg/µL), and their offspring were analyzed for alterations in body weight, adipose tissue morphology, thermogenesis, adipogenesis, and lipophagy. The findings revealed a notable reduction in birth weight and an increase in white adipocyte size in adult offspring mice. Notably, adult male mice exhibited BAT whitening, correlated with a negative dose-dependent downregulation of UCP1 expression, indicating thermogenesis dysfunction. Further investigation revealed augmented lipogenesis evidenced by the upregulation of FASN, SREBP-1c, CD36, and DGAT2 expression, coupled with the inhibition of lipophagy, indicated by elevated levels of mTOR, AKT, and p62 proteins and reduced levels of LC3II/LCI and Lamp2 proteins in male offspring. Conclusions: These findings indicate that gestational PSNP exposure plays a role in the development of obesity in offspring through the whitening of brown adipose tissue, which is triggered by lipogenesis and lipophagy inhibition, providing a novel insight into the metabolic risks associated with gestational PSNPs exposure.